Analisis Pendidikan Keterampilan Membatik bagi Warga Belajar Pendidikan Nonformal: Kajian Model Pendidikan di PKBM Mandiri Bakti. - Yulia Rahmawati; Norhidayat Norhidayat; Ridwan Ridwan; Arif Sugianto (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to examine in more depth how the Analysis of Batik Skills Education for Non-Formal Education Students: Study of the Education Model at PKBM Mandiri Bakti. This research approach employed qualitative research. Data collection methods included observation, interviews, and document study. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was validated using technical triangulation and source triangulation. The results indicate that this education model consists of several stages: (1) identifying learning needs based on the learners' backgrounds and local potential; (2) increasing awareness through motivation regarding the importance of cultural preservation and batik business opportunities; (3) transforming knowledge through a flexible time-block system that combines independent learning (modules and video tutorials), tutorials, and face-to-face sessions; and (4) fostering community independence through entrepreneurial mentoring. The study's conclusions indicate that the integration of local wisdom in skills education effectively increases technical knowledge and creativity in Dayak motifs, encourages economic independence in learners, and supports the sustainable preservation of East Kalimantan's cultural heritage.